Sekolah Ramah Anak: Sebuah Kajian Literatur - Fatahullah, M. Mirza; Sarwi, Sarwi; Sudarmin, Sudarmin; Cahyono, Adi Nur (Al Asma: Journal of Islamic Education, 2025)
Child-Friendly Schools (CFS) is an educational model designed to create an inclusive, safe, and supportive learning environment that fosters children's holistic development. This study aims to analyze the implementation, challenges, and impacts of the CFS model in various countries using a Systematic Literature Review (SLR) approach. Specifically, this research identifies the factors that contribute to the successful implementation of child-friendly schools and the obstacles encountered in different cultural and social contexts. The method used in this study is Systematic Literature Review (SLR), by reviewing and analyzing scientific articles published in nationally and internationally indexed journals over the last ten years. The articles analyzed were selected based on their relevance to the CFS concept, the quality of the publication, and the research methods used. The data from the selected articles were then synthesized to obtain key findings related to the implementation and challenges of CFS. The analysis results indicate that while CFS adheres to global principles such as inclusivity, safety, and participation, its implementation requires local adaptations according to the cultural and social context of each region. The main challenges identified include resource constraints, lack of continuous teacher training, and resistance to pedagogical change. Additionally, the involvement of stakeholders such as teachers, parents, and local communities has been found to be a crucial factor in the successful implementation of CFS. The study also finds that the application of CFS principles has a positive impact on students' learning motivation, social interactions, and academic achievements. Based on these findings, this study recommends strengthening child-rights-based policies, continuous teacher training, and cross-sectoral support to ensure the sustainability and effectiveness of CFS programs.